A busca por um marco processual da internet : requisitos para colheita dos dados armazenados em compartimentos eletrônicos - Costa Jr., Ivan Jezler (2018)
This paper analyzes the Civil Internet Framework in the context of the right to evidence in criminal proceedings. From the new technological resources of investigation energized by electronic compartments and by the Internet, the main legislative vacuums were pointed out in the orientation of these means of proof. There are no strong guiding rules, which contributed to a jurisprudential oscillation, with arbitrariness and decisionism in judicial decisions analyzed. In the pursuit of an absolute and anticipated truth, the trivialization of the hidden means of investigation had been demonstrated, even directly, when a public audience had been witnessed and concluded, which pursued the insertion of back door in applications with rigid encryption to propitiate the collection of communications stored in these telematic vehicles. The criminal prosecution organs questioned on this solemnity still supported the suppression of the rules of international cooperation for the collection of electronic data abroad. The distinction between interception and capture of conversations had still been drawn in a watertight manner. The general objective of the research is to analyze if the Civil Framework of the Internet presents itself as sufficient to regulate the capture of telematic data stored in electronic compartments. For that, a critical and multidisciplinary analysis of the themes was done, based on the consultation of scientific works and journalistic publications, and the documentary research was used to demonstrate the need to face the theme and the practical relevance of the theme, as attested by the analysis of the decisions of the Superior Courts and manifestations of other procedural subjects. As a result, the necessity of a proper legal regime for the search of digital data stored in electronic compartments was evidenced. The devices that regulate orthodox search and seizure do not have the ability to maintain the integrity and sameness of content volatile, tangible, and easily deteriorated. At the same time, in the wake of what had been commented on the ontological distinction between interception and informational search, the rule of Law no. 9,296, dated July 24, 1996, can not preserve the specificities of the collection of stored content. In this step, the application of the extensive and privileged interpretation, a taxation with protection in a constitutional hermeneutic, had been removed. It is concluded that the Civilian Internet Framework did not provide, with requirements and assumptions, the blind spot mentioned. There are no clear rules as to legitimacy, competence, reasoning and timing. This void provided the analysis of decisions of the first degree to the Federal Supreme Court, which evidenced the legal insecurity built by a non-existent or deficient legislation.